Silicon Fluxes in Upland Corn Agroecosystems - Anh, Nguyen Thi Quynh; Ngan, Nguyen Thi; Trung, Lai Quang; Hung, Doan Dinh; Van, Dinh Mai (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 4DO - 10.25073/2588-1094/vnuees.5327, 2025)
Silicon (Si) is a beneficial element for plant growth, particularly in monocotyledons like corn ( Zea mays ). In upland agroecosystems, where soil weathering and erosion rates are high, the role of corn in the silicon cycle is crucial. This study evaluates the contribution of corn to silicon dynamics by analyzing Si concentrations in plant tissues and various soil Si fractions across 24 upland sites in Northern Vietnam. Our results indicate that corn leaves accumulate more Si (x̅ = 10.9 g kg⁻¹) than stems (x̅ = 4.28 g kg⁻¹), highlighting leaves as the primary sink of Si within the plant. In soils, amorphous NaOH-extractable Si was 6.35 g kg⁻¹, while exchangeable Si and water-soluble Si had low average content (x̅ = 0.01 g kg⁻¹, x̅ = 0.03 g kg⁻¹, respectively), reflecting varying degrees of bioavailability. Spearman correlation analyses revealed positive relationships between exchangeable Si fractions in soil and plant Si uptake, especially in leaves. These findings emphasize the role of corn in sustaining Si fluxes in upland agriculture and underline the need for soil management practices that maintain Si availability for long-term ecosystem stability.